Boganmeldelser - Karl Johan Lång; Ian Taylor; Kauko Aromaa; Beth Grothe Nielsen; Per Ole Johansen; Inkeri Anttila; Yngve Hammerlin; Pekka Hakkarainen; Peter Gottlieb; Vagn Greve; Knut Papendorf; Sysette Vinding Kruse; et al. (Nordisk Tidsskrift for Kriminalvidenskab)
Intet resumé